Hypomania, Depression, Euthymia: New Evidence in Parkinson’s Disease - Margherita Canesi; Sara Lavolpe; Viviana Cereda; Alessandra Ranghetti; Roberto Maestri; Gianni Pezzoli; Maria Luisa Rusconi (Behavioural Neurology)
The field related to mood disorders in Parkinson’s disease (PD) is fragmented. The aim of this cohort observational study was to evaluate whether the episodes of mood alteration could appear in different disease stages and to verify how nonmotor symptoms were led off into different stages. We enrolled 93 PD outpatients (three groups: drug naive—DN; not exhibiting motor fluctuations—n-MF; and exhibiting motor fluctuations—MF) and 50 healthy controls. Mood state was assessed through the Internal State Scale (ISS) while depressive symptoms were evaluated through the Beck Depression Inventory-II (BDI-II), nonmotor symptoms by means of the Non-Motor Symptoms Scale (NMSS), and the presence of impulse control disorders (ICDs) with the Questionnaire for Impulsive-Compulsive Disorders in Parkinson’s Disease (QUIP). Clinical and pharmacological data have also been recorded. No significant differences in mood state distribution between groups were observed. Nevertheless, as regards the mood state distribution within groups, in n-MF (47.6%) and MF patients (50%), (hypo)mania presence was significantly higher than other symptoms. In DN patients, hypomania showed a prevalence of 38.1% although it was not significant. At least one ICD was reported in 29.3% of n-MF and 50% of MF patients. In the MF group, a moderate positive correlation between ISS ACTivation subscale scores and the presence of ICDs and compulsive medication use emerged. Finally, MF patients reported higher BDI-II total scores than DN. Our results show that mood alterations in PD, considering both depressive symptoms and mood elevation, are related to the advanced stages of the disease as well as the presence of ICDs, and dopaminergic therapy would not always be able to restore a normal mood condition.